2016
DOI: 10.4081/jlimnol.2015.1405
|View full text |Cite
|
Sign up to set email alerts
|

First observations of anthropogenic underwater noise in a large multi-use lake

Abstract: <p>Over the last fifty years, anthropogenic noise has increased dramatically in aquatic environments and is now recognised as a chronic form of pollution in coastal waters. However, this form of pollution has been largely neglected in inland water bodies. To date, very few studies have investigated the noise spectra in freshwater environments and at present no legislation exists to protect freshwater organisms from anthropogenic noise. The present study represents the first assessment of anthropogenic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The groundwork for this was laid in the 1960s, when the response of cutthroat trout ( Oncorhynchus clarkii ) to natural noise levels in Yellowstone National Park was described by Stober (); since then, alterations in the levels of underwater noise have been measured in both lakes and rivers (Stober ; Amoser and Ladich ; Bolgan et al . ). At the same time, an increasing number of studies have identified direct impacts of anthropogenic noise on fish behavior (eg Lugli et al .…”
Section: Listening To Key Aquatic Groups and Processesmentioning
confidence: 97%
See 1 more Smart Citation
“…The groundwork for this was laid in the 1960s, when the response of cutthroat trout ( Oncorhynchus clarkii ) to natural noise levels in Yellowstone National Park was described by Stober (); since then, alterations in the levels of underwater noise have been measured in both lakes and rivers (Stober ; Amoser and Ladich ; Bolgan et al . ). At the same time, an increasing number of studies have identified direct impacts of anthropogenic noise on fish behavior (eg Lugli et al .…”
Section: Listening To Key Aquatic Groups and Processesmentioning
confidence: 97%
“…Underwater acoustic monitoring and rivers (Stober 1969;Amoser and Ladich 2010;Bolgan et al 2016). At the same time, an increasing number of studies have identified direct impacts of anthropogenic noise on fish behavior (eg Lugli et al 2003), leading to the conclusion that noise can affect fish in multiple ways: by increasing stress levels, changing dispersal behaviors, and interfering with communication.…”
Section: Threat Monitoringmentioning
confidence: 99%
“…Aquatic environments are particularly vulnerable due to the relatively low attenuation of sounds in water (Parks et al., ; Tyack & Janik, ). Freshwater environments are subjected to noise coming from sediment extraction, motorised boats, recreational activities, and construction (Bolgan et al., ). Noise pollution can result in injuries such as hearing loss, internal bleeding, or even death (Popper & Hastings, ; Popper & Hawkins, ; Popper et al., ), mask communication signals (Fletcher, ), or affect population sizes and density (Laiolo, ).…”
Section: Study Areas For Pam: Freshwater Ecoacousticsmentioning
confidence: 99%
“…Measurements of the extent of anthropogenic noise in freshwater environments are still scarce (Bolgan et al., ). Predictive models of noise propagation are powerful tools for estimating the spread of noise impacted areas.…”
Section: Study Areas For Pam: Freshwater Ecoacousticsmentioning
confidence: 99%
“…Freshwater bioacoustics to date has focussed less on ecological context, but mainly dealt with mechanistic descriptions of sound reception and sound production, as well as behavioural studies about communications (see Fine & Parmentier, ; Ladich, for overviews of the respective fields). A third group of studies has mainly researched the effect of noise on underwater organisms (Amoser & Ladich, ; Bolgan et al, ; see Popper & Hawkins, for a recent review).…”
mentioning
confidence: 99%